Functional consequences of a mutation in an expressed human alpha-cardiac actin at a site implicated in familial hypertrophic cardiomyopathy. - Bookwalter, C.S.; Trybus, K.M. (Journal of Biological Chemistry, 2006)
Point mutations in human alpha-cardiac actin cause familial hypertrophic cardiomyopathy. Functional characterization of these actin mutants has been limited by the lack of a high level expression system for human cardiac actin. Here, wild-type (WT) human alpha-cardiac actin and a mutant E99K actin have been expressed and purified from the baculovirus/insect cell expression system. Glu-99 in subdomain 1 of actin is thought to interact with a positively charged cluster located in the lower 50-kDa domain of the myosin motor domain. Actin-activated ATPase measurements using the expressed actins and beta-cardiac myosin showed that the mutation increased the K(m) for actin 4-fold (4.7 +/- 0.7 mum for WT versus 19.1 +/- 3.0 mum for the mutant), whereas the V(max) values were similar. The mutation slightly decreased the affinity of actin for S1 in the absence of nucleotide, which can partly be accounted for by a slower rate of association. The in vitro motility for the E99K mutant was consistently lower than WT over a range of ionic strengths, which is likely related to the lower average force supported by the mutant actin. The thermal stability of the E99K was comparable to that of WT-actin, implying no folding defects. The lower density of negative charge in subdomain 1 of actin therefore weakens the actomyosin interaction sufficiently to decrease the force and motion generating capacity of E99K actin, thus providing the primary insult that ultimately leads to the disease phenotype.